Optimum Condition of Ni2+ Cation Desorption from Adsorbent Sulfonate-modified Silica gel-GPTMS - Kauri, Desrike; Oktavia, Budhi; Sari, Trisna Kumala; Khair, Miftahul (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Silica gel is a compound that has two active sides, namely silanol (S-OH) and siloxane (Si-O-Si), which are still less effective as adsorbents, so modification is carried out. Silica is modified by adding sulfonate compounds with the help of GPTMS bridging compounds. This modification aims to improve the absorption capacity of Nickel (Ni2+) metal ions in the modified adsorbent, namely sulfonate-modified silica gel-GPTMS. The characterizations used are SSA (Atomic Absorption Spectrophotometry) to see the success of the adsorption and desorption process. This research is quantitative experimental research where the adsorption and desorption processes are carried out using the column method, where the adsorption process itself is carried out on the Ni2+ cation using silica gel-GPTMS Sulfonate adsorbent at an optimal concentration of 20 ppm and pH 3. Then, we continued with the desorption process, which aims to determine the optimum conditions of the desorption process, including determining the type of desorption agent (NaCl and CaCl2) and concentration for the Ni2+ cation desorption process. Based on the results of the research conducted, the optimum condition of the type of desorption agent is CaCl2 where the desorbed weight is 0.1527 mg, and the per cent desorption is 90.10%, the optimum concentration of CaCl2 is 0.025M with a desorbed weight of 0.1442 mg and a per cent desorption of 90.18%. Based on the experimental results, the sulfonate-modified silica gel-GPTMS adsorbent can still be used repeatedly for adsorption and desorption of Ni2+ cations at optimum conditions.